A High-Rate Two-Dimensional Polyarylimide Covalent Organic Framework Anode for Aqueous Zn-Ion Energy Storage Devices - Yu, Minghao; Chandrasekhar, Naisa; Raghupathy, Ramya Kormath Madam; Ly, Khoa Hoang; Zhang, Haozhe; Dmitrieva, Evgenia; Liang, Chaolun; Lu, Xihong; Kühne, Thomas D.; Mirhosseini, Hossein; Weidinger, Inez M.; Feng, Xinliang (Journal of the American Chemical Society, 2020)
Rechargeable aqueous Zn-ion energy storage devices are promising candidates for next-generation energy storage technologies. However, the lack of highly reversible Zn2+-storage anode materials with low potential windows remains a primary concern. Here, we report a two-dimensional polyarylimide covalent organic framework (PI-COF) anode with high-kinetics Zn2+-storage capability. The well-organized pore channels of PI-COF allow the high accessibility of the build-in redox-active carbonyl groups and efficient ion diffusion with a low energy barrier. The constructed PI-COF anode exhibits a specific capacity (332 C g-1 or 92 mAh g-1 at 0.7 A g-1), a high rate capability (79.8% at 7 A g-1), and a long cycle life (85% over 4000 cycles). In situ Raman investigation and first-principle calculations clarify the two-step Zn2+-storage mechanism, in which imide carbonyl groups reversibly form negatively charged enolates. Dendrite-free full Zn-ion devices are fabricated by coupling PI-COF anodes with MnO2 cathodes, delivering excellent energy densities (23.9 ∼66.5 Wh kg-1) and supercapacitor-level power densities (133 ∼4782 W kg-1). This study demonstrates the feasibility of covalent organic framework as Zn2+-storage anodes and shows a promising prospect for constructing reliable aqueous energy storage devices.
CRIS-Team Scopus Importer:2022-04-14